SOCIO-ECOLOGICAL FOUNDATIONS OF INTERCULTURAL COMMUNICATION STUDIES OF IN THE CONDITIONS OF GLOBALIZATION - Semenovna Avramkova, Irina; Ivanovna Anufrieva, Natalia; Vladlenovich Kamyanets, Alexander; Elena Olegovna, Kuznetsova; Scherbakova, Anna (Revista Inclusiones, 2020)
The article examines the ecologically significant social interaction situations as the opportunities for the productive study of intercultural communication in the conditions of globalization. The existing gaps between the communication processes and real interactions between communicants that have increased in the globalization era due to the development of virtual reality that supersedes direct interpersonal contacts in the intercultural dialogue are identified. The authors, therefore, investigate the opportunities of overcoming these gaps through the inclusion of intercultural communications in the context of real social interactions significant for the self-preservation and survival of individuals in the face of new challenges and risks of globalization. In this context, the various levels and situations of social interaction accompanied by the corresponding socio-ecologically significant communicative acts are indicated. The works of social phenomenologists and the achievements of social constructivism and frame theory are viewed as the closest sources of this approach to the study of intercultural communications. The corresponding research strategy described in the article may be of interest to a wide range of specialists and researchers in the field of intercultural communications and social interaction.